Distribution and Localization of Gold in Meguma Group Rocks, Nova Scotia: Implications of Metal Distribution Patterns in Quartz Veins and Host Rocks on Mineralization Processes at Harrigan Cove, Halifax County - Crocket, J.; Fueten, F.; Clifford, P. (Atlantic Geology, 1986)
The contents of Au, As, Sb and W in metagreywacke, slate and quartz veins from Harrigan Cove, Halifax County, N.S. were determined by neutron activation analysis. The gold-bearing veins in the Goldenville Formation, the lower sandy flysch member of the Cambro-Lower Ordovician Meguma Group of eastern Nova Scotia. The Harrigan Cove metagreywacke and slate are strongly enriched in arsenic (as arsenopyrite) and weakly enhanced in gold relative to similar lithologies in barren Meguma terranes. Creywacke is the main sink for arsenic while gold occurs in highest concentration in greywacke and slate, but not in the quartz veins- Anomalous gold values occur with the same frequency in greywacke, slate and quartz veins, but anomalous quartz vein samples are much richer in gold than anomalous host rock samples. It is suggested that the metal distributions support a polygenetic origin for the mineralization, whereby early arsenic- and sulphur-bearing fluids introduce arsenopyrite and sulphides, mainly into greywacke. Gold is concentrated by these minerals and later mobilized along with large quantities of silica early in the history of deformation through pressure solution processes which generate a spaced cleavage. These silicic fluids and their metals are then injected by hydraulic fracture, mainly into slate, to form the gold-bearing bedding-parallel quartz veins.